2015
DOI: 10.1007/s10661-015-4912-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of phytoplankton bloom dynamics by citizen scientists in urban and peri-urban environments

Abstract: Freshwater ecosystems are severely threatened by urban development and agricultural intensification. Increased occurrence of algal blooms is a main issue, and the identification of local dynamics and drivers is hampered by a lack of field data. In this study, data from 13 cities (250 water bodies) were used to examine the capacity of trained community members to assess elevated phytoplankton densities in urban and peri-urban freshwater ecosystems. Coincident nutrient concentrations and land use observations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 73 publications
1
24
0
1
Order By: Relevance
“…An example of the use of instruments for obtaining crowdsourced surface water data is given in Sahithi (), who showed that a mobile app and lake monitoring kit can be used to measure the physical properties of water samples. Another application is given in Castilla et al (), who showed that the data from 13 cities (250 water bodies) measured by trained citizens with the aid of instruments can be used to successfully assess elevated phytoplankton densities in urban and peri‐urban freshwater ecosystems.…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
“…An example of the use of instruments for obtaining crowdsourced surface water data is given in Sahithi (), who showed that a mobile app and lake monitoring kit can be used to measure the physical properties of water samples. Another application is given in Castilla et al (), who showed that the data from 13 cities (250 water bodies) measured by trained citizens with the aid of instruments can be used to successfully assess elevated phytoplankton densities in urban and peri‐urban freshwater ecosystems.…”
Section: Review Of Crowdsourcing Data Acquisition Methods Usedmentioning
confidence: 99%
“…In this last example, the occurrence of one of the amphibian species (the wood frog Lithobates sylvaticus) was positively associated with high levels of nitrogen. High levels of nutrients (and eutrophication) are also known to be a key driver of cyanobacterial presence and blooms in urban ponds (Peretyatko et al 2010, Vincent and Kirkwood 2014, Waajen et al 2014, Castilla et al 2015, Lurling et al 2017. This is a particularly deleterious impact of eutrophication in urban areas, as some cyanobacteria produce toxins which can be harmful to people and their pets.…”
Section: Water Qualitymentioning
confidence: 99%
“…Fluctuation in water level was assessed as the proportion of observations recorded as low or high on a three-point scale (i.e., not average). The presence or absence of algal blooms was averaged across samples within each season and each site as a proxy for algal bloom frequency [35]. [36,37] Independent testing [33,38] Manual database checking protocol [37] Photographs…”
Section: Field Measurementsmentioning
confidence: 99%
“…Citizen observatories have previously been identified as a potentially powerful tool for the monitoring of algal blooms [35,68] with a suite of applications now having being developed to facilitate their record such as CyanoTRACKER (University of Georgia), Bloomin' Algae (Centre for Ecology and Hydrology), and bloomWatch (US EPA). The present study suggests that potential local scale drivers may also be monitored by citizen scientists.…”
Section: Influence Of Urbanisationmentioning
confidence: 99%